Distribusi Moisture Content Pada Zona Perakaran Tanaman (Zona Tidak Jenuh) Perkebunan Teh Gambung, Bandung Selatan - Candra, Adi (Jenderal Soedirman University, 2012)
Research on moisture content distribution in the root zone is intended to determine the moisture content in accordance with tea plant and its distribution pattern. Measurement of moisture content by using gypsum block as media liaison between the soil and water in the soil moisture is conducted by means Bouyoucos Soil Meter. Moisture content is obtained by performing measurements on a laboratory and field scale. Laboratory scale test is emphasized on calibration of the gypsum block to be applied in the measurement field. Site measurement was made in three drill holes, each 150 cm in depth, which are at peak, slopes and valleys in the study area that had been predetermined. The result of research shown that high moisture content about 50% â95% which tends to increase downward modeling on moisture content has similar result to the field measurement. Tea plants needed of relative large moisture content, since it requires a moisture content continuosly and yields of tea leave.